Harmonisation of Outcome Parameters and Evaluation (HOPE) for actinic keratosis: protocol for the development of a core outcome set - Heppt, Markus V.; Steeb, Theresa; Schmitz, Lutz; Garbe, Claus; French, Lars E.; Leiter, Ulrike; Berking, Carola (Trials, 2019)
BACKGROUND: Actinic keratoses (AK) are common skin lesions that can progress to invasive squamous cell carcinoma of the skin. A variety of lesion- or field-targeted treatment options exist and their efficacy has been demonstrated in numerous randomised controlled trials (RCTs). However, the reported endpoints are highly heterogeneous, making it difficult to assess and compare distinct treatment options and to reach an evidence-based choice of therapy. METHODS: A systematic literature search will be conducted to analyse which endpoints are reported in RCTs. The focus will be on effectiveness, tolerability, cosmesis, and patient satisfaction. The reported endpoints of these studies, as well as their frequency and data collection times, will be documented in a standardised way to generate a comprehensive list of reported endpoints. In order to complete the identified outcomes in the literature search, focus groups on affected patients and structured interviews with board-certified dermatologists will be conducted to identify both patient- and practice-relevant endpoints. After the identification phase, the evaluation of the endpoints follows. In a two-stage Delphi procedure, experts including patient representatives will evaluate the endpoints in a standardised and transparent manner. A final face-to-face consensus meeting will be conducted after the last Delphi round in which a final list of core outcomes will be consented. DISCUSSION: The development of a standardised endpoint set for the treatment of AK will contribute to improving the comparability of therapeutic options. Our catalogue will enhance the synthesis of evidence for the future by reducing heterogeneity in outcomes between RCTs and hence contribute to improving the quality of research, evidence-based and patient-centred treatment. TRIAL REGISTRATION: Core Outcome Measures for Effectiveness ( COMET ) database. Registered in December 2018.
EVALuna2:209212